An Initial Analysis of the Job Polarization in Vietnam - Huong, Vu Thanh; Dai, Tang Duc (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2017)
By adopting the methods of occupation classification and job classification by skill of the International Labour Organization’s and the method of skill mismatch identification, the paper analyzes the job polarization in Vietnam in the 2009-2015 period. It is shown in the research that job polarization has signs to occur in Vietnam, and more clearly for male workers and in rural areas. There are two major reasons for the job polarization in Vietnam including scientific and technological advancements and economic globalization. The job polarization has also resulted in skill mismatch in Vietnam. Therefore, the implications proposed in the paper focus on thorough observation and analysis on labor market, improvement of labor skills and promotion of close cooperation among policy makers, labor users and training institutions so as to recognize, identify and alleviate negative impacts of the labor polarization in Vietnam. Keywords Skills mistmach, job polarization, Vietnam References [1] Goos, Maarteen, Manning, Alan, “Lousy and Lovely Jobs: The Rising Polarization of Work in Britain”, The Review of Economics and Statistics, 89 (2007) 1, 118-133. [2] Autor, David H., Lawrence F. Katz và Kearney, Melissa S., “The Polarization of the U.S. Labor Market”, American Economic Review Papers and Proceedings, 96 (2006) 2, 189-194. [3] Abel, Jaison R., Deitz, Richard, “Job polarization and rising inequality in the nation and the New York - Northern New Jersey Region”, Curreny Issues in Economics and Finance, 18 (2012) 7, 1-7. [4] Sparreboom, Theo & Tarvid, Alexander, “Imbalanced Job Polarization and Skills Mismatch in Europe”, Journal of Labour Market Res, 49 (2016), [5] ILO, “International Standard Classfication of Occupation Volume 1: Structure, group definitions and correspondence tables”, Geneva: International Labour Organization, 2012. [6] ILO, “Who are Viet Nam’s 18 million wage workers?”, Hanoi: International Labour Organization, 2015. [7] Nguyễn Bá Ngọc và Phạm Minh Thu, “Năng suất lao động Việt Nam nhìn từ góc độ cơ cấu lao động và kỹ năng”, Bản tin Khoa học, 41 (2014), 4. [8] ILO & ILSSA, “Lao động trình độ cao - Nhân tố quyết định để phát triển bền vững đất nước”, Bản tin tóm tắt chính sách, 1 (2014). [9] Ban Kinh tế Trung ương, “Báo cáo tổng kết một số vấn đề lý luận - thực tiễn qua 30 năm đổi mới (1986-2016) về đẩy mạnh công nghiệp hóa - hiện đại hóa đất nước”, Hà Nội, 2014. [10] Nguyễn Anh Thu, Vũ Thanh Hương, Nguyễn Thị Thanh Mai, “Cải thiện tiếp cận của Doanh nghiệp vừa và nhỏ Việt Nam với các hỗ trợ đổi mới công nghệ”, Hiệp hội Doanh nghiệp đầu tư nước ngoài, Hà Nội, 2017. [11] ILO, “ASEAN trong quá trình chuyển đổi: Công nghệ đang làm thay đổi việc làm và doanh nghiệp như thế nào”, Báo cáo tóm tắt về Việt Nam, Hà Nội, 2016. [12] Tổng cục Thống kê, Số liệu thống kê, truy cập ngày 10/3/2017, từ http://www.gso.gov.vn/Default.aspx?tabid=706&ItemID=13412. [13] Nguyễn Hồng Sơn, Nguyễn Cẩm Nhung, Vũ Thanh Hương và Nguyễn Thị Minh Phương, “Kinh tế thế giới và Việt Nam năm 2016, triển vọng năm 2017 và một số gợi ý chính sách cho Việt Nam”, Tạp chí Khoa học Đại học Quốc gia Hà Nội: Kinh tế và Kinh doanh, 32 (2016) 4, 1-11. [14] Tổng cục Hải quan, “Xuất nhập khẩu hàng hóa tháng 12 và 12 tháng năm 2016”, truy cập ngày 10/3/2017, từ <https://customs.gov.vn/Lists/ThongKeHaiQuan/ViewDetails.aspx?ID=1038&Category=Phân%20t%C3%ADch%20định%20kỳ&Group=Phân%20t%C3%Adch>.